Critical balance in magnetohydrodynamic, rotating and stratified turbulence: towards a universal scaling conjecture - Nazarenko, S; Schekochihin, A (2011)
It is proposed that critical balance a scale-by-scale balance between the linear propagation and nonlinear interaction time scales can be used as a universal scaling conjecture for determining the spectra of strong turbulence in anisotropic wave systems. Magnetohydrodynamic (MHD), rotating and stratified turbulence are considered under this assumption and, in particular, a novel and experimentally testable energy cascade scenario and a set of scalings of the spectra are proposed for low-Rossby-number rotating turbulence. It is argued that in neutral fluids the critically balanced anisotropic cascade provides a natural path from strong anisotropy at large scales to isotropic Kolmogorov turbulence at very small scales. It is also argued that the k -2 spectra seen in recent numerical simulations of low-Rossby-number rotating turbulence may be analogous to the k -3/2 spectra of the numerical MHD turbulence in the sense that they could be explained by assuming that fluctuations are polarised (aligned) approximately as inertial waves (Alfvén waves for MHD). © 2011 Cambridge University Press.